[Modeling dark puffs using P-transposons in Drosophila melanogaster polytene chromosomes] - Semeshin, V.F.; Shloma, V.V.; Beliaeva, E.S.; Zhimulev, I.F. (Genetika, 2001)
Modeling of morphologically unusual "dark" puffs was conducted using Drosophila melanogaster strains transformed by construct P[ry; Prat:bw], in which gene brown is controlled by the promoter of the housekeeping gene Prat. In polytene chromosomes, insertions of this type were shown to form structures that are morphologically similar to small puffs. By contrast, the Broad-Complex (Br-C) locus, which normally produce a dark puff in the 2B region of the X chromosome, forms a typical light-colored puffs when transferred to the 99B region of chromosome 3R using P[hs-BRC-z1]. A comparison of transposon-induced puffs with those appearing during normal development indicates that these puff types are formed via two different mechanisms. One mechanism involves decompaction of weakly transcribed bands and is characteristic of small puffs. The other mechanism is associated with contacts between bands adjacent to the puffing zone, which leads to mixing of inactive condensed and actively transcribed decondensed material and forming of large dark puffs.